Easily Erectable Prefabricated Solid Waste Recycling Processing Plants (WRPP) with High Temperature Pyrolysis (HTP) Technology for Sub-Saharan Africa - Frank Michael, Adam; Frank, Kavishe; Yuri, Kazakov; Arkadij , Melnikov (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2018)
Every State has the obligation to promote and maintain the welfare of its people and that all people have the right to live in a clean, healthy environment through sustainable and effective waste management¹. The option for waste management that provides the most benefit or causes the least damage to the environment as a whole, at a cost acceptable to society, in the short term and long term, must be adopted to reduce the generation of waste and polluting substances at source. This means that the reduction, re-use and recycling of waste must be promoted.